2020
DOI: 10.1111/avj.12957
|View full text |Cite
|
Sign up to set email alerts
|

Citizens' juries give verdict on whether private practice veterinarians should attend unvaccinated Hendra virus suspect horses

Abstract: Background Hendra virus (HeV) is endemic in Australian flying foxes, posing a threat to equine and human health. Equine vaccination remains the most effective risk mitigation strategy. Many horses remain unvaccinated – even in higher‐risk regions. Debate surrounding the vaccine's use is characterised by conflicting perspectives, misunderstanding and mistrust. Private veterinary practitioners are critical to early identification of public health risk through recognition, sampling and management of suspect‐equin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Some practitioners referred to funding assistance available through the National Significant Disease Investigation Program; however, the remit of this programme is predominantly focused on livestock and wildlife diseases, extending to companion animals in only some state jurisdictions (Animal Health Australia [AHA], 2019; Annand et al., 2020). The lack of structured assistance available to small animal practitioners—in particular access to free or subsidized pathology testing through government laboratories—has real potential to heighten vulnerability to an emerging disease outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some practitioners referred to funding assistance available through the National Significant Disease Investigation Program; however, the remit of this programme is predominantly focused on livestock and wildlife diseases, extending to companion animals in only some state jurisdictions (Animal Health Australia [AHA], 2019; Annand et al., 2020). The lack of structured assistance available to small animal practitioners—in particular access to free or subsidized pathology testing through government laboratories—has real potential to heighten vulnerability to an emerging disease outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…This often related to concerns about the possible risk of infection to themselves and others, along with unfamiliarity with appropriate procedures and support available from government veterinarians. Such concerns could be driven by experiences with Hendra virus, which resulted in veterinarians leaving equine practice due to personal health concerns, as well as work health and safety responsibilities and threat of litigation when managing potential and confirmed Hendra virus cases in horses (Annand et al., 2020; Mendez et al., 2017). These findings need to be considered in light of a recent study showing a high prevalence of imposter syndrome, the tendency to doubt one's abilities despite positive evidence to the contrary, amongst veterinarians (Kogan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Citizen juries have been used to elicit the views of well-informed people on various control measures for reducing the risks associated with HeV infection. 15,16 Three juries reported that, although ecological strategies should be included in HeV risk management strategies, currently recommended interventions, including vaccination and changing horse husbandry practices, must remain a high priority. 16 Jurors acknowledged that HeV management posed an important challenge for private veterinarians, but the majority of jurors believed that veterinarians should not be obliged to attend unvaccinated horses.…”
mentioning
confidence: 99%
“…16 Jurors acknowledged that HeV management posed an important challenge for private veterinarians, but the majority of jurors believed that veterinarians should not be obliged to attend unvaccinated horses. 15 One of the major difficulties facing vets is that the communication of the risks associated with HeV infection and the consequences of not vaccinating horses against this virus needs to be carried out in advance of the horse becoming sick. Although many vets have ready access to information for clients, and the majority inform clients about HeV-related risks when a horse appears sick, 17 by the time a vet is called to attend a sick horse, it is too late to discuss whether the horse should be vaccinated against Hendra.…”
mentioning
confidence: 99%
See 1 more Smart Citation